Ngapartji Ngapartji: In turn, in turn: Ego-histoire, Europe and Indigenous Australia - Castejon, Vanessa; Cole, Anna; Haag, Oliver; Hughes, Karen (ANU Press, 2014)
In this innovative collection, Indigenous and non-Indigenous scholars from Australia and Europe reflect on how their life histories have impacted on their research in Indigenous Australian Studies. Drawing on Pierre Nora's concept of ego-histoire as an analytical tool to ask historians to apply their methods to themselves, contributors lay open their paths, personal commitments and passion involved in their research.